The influence of two light-temperature regimes on the development of Scheepers wheat up to the stage of ear emergence - Beukes, David Nicolaas (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1963.